PpBZR1, a BES/BZR transcription factor, enhances cold stress tolerance by suppressing sucrose degradation in peach fruit - Zhang, Shiyun (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.